DEEPEN (Droichead: Exploring and Eliciting Perspectives, Experiences and Narratives) - Uí Choistealbha, Julie; Ní Dhuinn, Melanie; Kaur, Tandeep; Garland, Shelli Ann (The Teaching Council, 2021)
The DEEPEN, (Droichead: Exploring and Eliciting Perspectives, Experiences, and Narratives) research study sought to explore and elicit perspectives, experiences and narratives of newly qualified teachers (NQTs) and other school personnel participating in the Droichead process in Irish primary and post-primary schools.
Keywords: Induction; Newly qualified teachers; Mentoring; Teacher Education; initial teacher education; Early career teachers; Education; Education--Ireland